Cr(vi) removal by mesoporous FeOOH polymorphs: performance and mechanism. Issue 85 (30th August 2016) - Wu, Shijiao; Lu, Jianwei; Ding, Zecong; Li, Na; Fu, Fenglian; Tang, Bing
Abstract : The mesoporous FeOOH polymorphs, i.e., goethite (α-FeOOH), akaganeite (β-FeOOH), lepidocrocite (γ-FeOOH), and feroxyhyte (δ-FeOOH) were synthesized and characterized before and after reaction with Cr(vi ) using various analytical techniques. Abstract : The mesoporous FeOOH polymorphs, i.e., goethite (α-FeOOH), akaganeite (β-FeOOH), lepidocrocite (γ-FeOOH), and feroxyhyte (δ-FeOOH) were synthesized and characterized before and after reaction with Cr(vi ) by scanning electron microscopy (SEM), N2 adsorption–desorption isotherms, X-ray diffraction (XRD), saturation magnetization measurements, and X-ray photoelectron spectroscopy (XPS). The Cr(vi ) removal efficiencies by these four FeOOH polymorphs were investigated. After reaction for 120 min, the Cr(vi ) removal efficiencies by α-FeOOH, β-FeOOH, γ-FeOOH, and δ-FeOOH were 94.5%, 52.0%, 100%, and 84.6%, respectively. The Cr(vi ) removal efficiencies by these four FeOOH polymorphs were influenced by their specific surface area. The XPS analysis indicated that the removal of Cr(vi ) by these FeOOH polymorphs was a process of electrostatic attraction and ligand exchange. The study of this paper can reveal the reaction mechanism of FeOOH with Cr(vi ) and the different behaviors of the four FeOOH polymorphs in the removal of Cr(vi ).